Answer:
(–6, –4)
Explanation:
This pair of linear equations may be solved simultaneously by using the elimination method. This will involve ensuring that the coefficient of one of the unknown variables is the same in both equations.
It may be solved by substitution in that one of the variable is made the subject of the equation and the result is substituted into the second equation.
Using the substitution method, make y the subject in the first equation
y = 5x + 26
substitute into the second equation
2x -7(5x + 26) = 16
-33x - 182 = 16
-33x = 16 + 182
-33x = 198
x = 198/-33
x = -6
since y = 5x + 26
y = 5(-6) + 26
= -30 + 26
= -4
hence (x,y) = (-6,-4)